Sonochemical Reactions - Karakuş, Selcan (IntechOpen, 2020)
This book was written by authors in the field of ultrasound-assited synthesis and their applications. Among others, some of the topics covered are: ultrasound-assited synthesis of metal/metal oxide nanoparticles, graphene nanosheets, and ultrasound applications. In this book, authors focused on recent studies, applications, and new technological developments on fundamental properties of the ultrasound process.